Authenticating edible oils using fourier transform infrared spectroscopy: a review - Mohd Ali, Nurul Azarima; Tukiran, Nur Azira; Roslan, Raihanah (Penteract Technology, 2024)
Oil authentication has been widely discussed in recent years. One of the issues is the usage of gutter oil. This happened in China where many of the street foods were prepared using oils from sewage, gutters, and restaurant fryers. Other concerning issues including the adulteration of high-quality edible oils with cheaper oils and fresh palm oil with recycled cooking oil are common problems related to oil fraud. This may provoke the safety and the rights of public consumers. Hence, advanced, efficient, and rapid technology such as Fourier Transform Infrared Spectroscopy (FTIR) is needed to overcome the limitations of other technologies such as differential scanning calorimetry (DSC), gas chromatography-mass spectrometry (GC-MS) and high-performance liquid chromatography (HPLC) in analysing edible oils’ quality parameters, authentication, safety, stability and in foods related to oils. This review discusses the uses of FTIR in the analysis of edible oils and their authentication.